Encuesta sobre las regulaciones de los luci hispanos (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A series of documented examples of luci on the Iberian Peninsula are examined. Norms that could have regulated entrance into such sacred forests and the use of their internal resources are proposed as well.
Keywords: Celtiberians; Sacred Forests; Sacred Laws; Regulations; Inscriptions